Infant respiratory infections and later respiratory hospitalisation in childhood - Moore, H.; Hall, Graham; De Klerk, N. (European Respiratory Society, 2015)
Acute respiratory infections (ARI) cause significant morbidity in infancy. We sought to quantify the relationship between ARI and development of respiratory morbidity in early childhood. Population-based longitudinal hospitalisation data were linked to perinatal, birth and death records for 145 580 Western Australian children from 1997 to 2002. We conducted Cox regression with sensitivity analyses to quantify the risk of recurrent ARI in infancy for respiratory hospitalisation after the age of 3 years. ARI in infancy was significantly related to respiratory hospitalisation before (hazard ratio (HR) 3.5, 95% CI 3.1–3.8) and after (HR 3.0, 95% CI 2.6–3.4) adjusting for known risk factors including maternal smoking during pregnancy, season of birth, delivery mode and gestational age. We noted a dose response with the number and length of infant ARI hospitalisations and increasing risk with no effect modification by gestational age. Results were similar when later respiratory hospitalisations were restricted to asthma hospitalisations only. Recurrent hospitalisations for ARI in infancy significantly increase the risk of respiratory morbidity and asthma requiring hospitalisation after the age of 3 years in a dose-response fashion. The increase in relative risk is not modified by gestational age. Efforts to reduce the occurrence of infant ARI are likely to have significant public health benefits.